Analisis Kesalahan Berbahasa Pada Makalah Mahasiswa Prodi Pendidikan Ekonomi Fakultas Ekonomi UNIMED - Debora Debora; Friska Yani Natalia Hutasoit; Rindy Any Br Tarigan; Romiana Br Situmorang; Rut Yemima Sitorus; Wisman Hadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article discusses the analysis of language errors in students' papers in the Economic Education Study Program, Faculty of Economics, Medan State University. This research uses a descriptive qualitative method by analyzing and describing the types of language errors found in 10 student papers of the Economics education study program, Faculty of Economics, Medan State University. By collecting data in the form of student papers as samples, identifying and classifying the types of language errors , as well as describing and interpreting the findings. The research results identified four main categories of errors, namely errors in writing letters, words, punctuation marks, and absorption elements. In-depth analysis is carried out by classifying each error category into more specific types along with examples and corrections. These findings show the importance of understanding and mastering good and correct Indonesian language rules in writing scientific papers, especially for students. It is hoped that this research can provide valuable information for teachers and related institutions to improve students' language skills in writing quality scientific papers.